2012
DOI: 10.3174/ajnr.a3325
|View full text |Cite
|
Sign up to set email alerts
|

Yield of CT Angiography and Contrast-Enhanced MR Imaging in Patients with Dizziness

Abstract: BACKGROUND AND PURPOSE:Dizziness is a common symptom in emergency and outpatient settings. The purpose of our study was to compare the diagnostic and therapeutic efficacy of CTA of the head and neck, contrast-enhanced MR imaging of the brain (CE-MR), and contrast-enhanced MR imaging of the internal auditory canals and temporal bones in patients with isolated dizziness, to determine which of these modalities should be preferred in the evaluation of dizziness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 34 publications
0
23
0
3
Order By: Relevance
“…carotid stenosis and intracranial aneurysms) as well as allowing a post-contrast acquisition of the head for assessment of pathological enhancement. Regarding the use of CTA in patients with acute dizziness, Fakhran et al 19 described a diagnostic efficacy of CTA of 2.2% with a therapeutic efficacy of 1.3%. On the other hand, Chen et al 20 found that the presence of calcifications on CTA is a factor that could predict an ischaemic stroke but does not improve the sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…carotid stenosis and intracranial aneurysms) as well as allowing a post-contrast acquisition of the head for assessment of pathological enhancement. Regarding the use of CTA in patients with acute dizziness, Fakhran et al 19 described a diagnostic efficacy of CTA of 2.2% with a therapeutic efficacy of 1.3%. On the other hand, Chen et al 20 found that the presence of calcifications on CTA is a factor that could predict an ischaemic stroke but does not improve the sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Ahsan et al, [ 1 ] found 6.17% positive findings and 0.74% clinically significant findings for patients who were examined with CT or MR; they included patients with vertigo and dizziness, excluded patients with a history of stroke, brain tumour, brain surgery and other neurological disorder. Fakhran et al, [ 20 ] reported 3% positive findings on CT and MR examination performed with contrast; they excluded patients with the focal neurological deficit. Our research revealed 6.9% of clinically significant emergency examinations in patients with vertigo, without focal neurological abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…5,7 Einungis um eða undir 1% af sjúklingum með svima án annarra taugaeinkenna greinast með slag eða aðra alvarlega miðtauga-kerfissjúkdóma. 1,4,6,8 Í okkar rannsókn var ítarlegum upplýsingum um einkenni ekki safnað, svo sem um staðbundin taugaeinkenni, og því erfitt að meta réttmaeti TS í hverju tilfelli fyrir sig. Stað-haefa má þó að steinaflakk sé í flestum tilfellum haegt að greina á tiltölulega einfaldan hátt með klínískri skoðun.…”
Section: Umraeðaunclassified
“…Yfirgnaefandi meirihluti bráða-TS rannsókna af heila hjá sjúk-lingum með svima er pantaður af laeknum bráðadeilda 6 og gera má ráð fyrir að sú sé einnig raunin á slysa-og bráðadeild Landpít-ala. Kostnaðurinn við TS af heila (án skuggaefnis) á Landspítala er um það bil 58.000 kr. Á þessu fjögurra mánaða rannsóknartímabili voru gerðar 65 TS hjá svimasjúklingum á slysa-og bráðadeild og kostnaður heilbrigðiskerfisins vegna þeirra því um 3.770.000 kr.…”
Section: Umraeðaunclassified